Analysis of High School Students' Mathematical Creative Thinking Ability Levels in Solving Mathematical Problems - Larasati Tiara Medyasari; Zaenuri Zaenuri; Nuriana Rachmani Dewi; Kristina Wijayanti (Universitas Negeri Semarang, 2022)
Mathematical creative thinking ability is an important ability that must be possessed in the 21st century. This study aims to obtain an overview of the level of students' mathematical creative thinking abilities. The research sample was 31 students of class XI MIPA 1. This type of research is qualitative research. The instrument used is a test of the description of creative thinking skills, observation, documentation, and interviews. Data analysis techniques are carried out by reducing data, presenting data, and drawing conclusions and using triangulation techniques. The results showed 3 students were at the level of creative thinking ability level 4 (very creative), 5 people were at level 3 (creative), 10 people were at level 2 (less creative) and 13 people were at level 1 creative thinking ability (less creative).